UNIT 7.34 Cell Proliferation Method: Click Chemistry Based on BrdU Coupling for Multiplex Antibody Staining. Issue 1 (1st April 2015) - Cappella, Paolo; Gasparri, Fabio; Pulici, Maurizio; Moll, Jürgen
Abstract : Determination of incorporation of the thymidine analog 5‐bromo‐2′‐deoxyuridine (BrdU) into DNA is a widely used method to analyze the cell cycle. However, DNA denaturation is required for BrdU detection with the consequence that most protein epitopes are destroyed and their immunocytochemical detection for multiplex analysis is not possible. A novel assay is presented for identifying cells in active S‐phase that does not require the DNA denaturation step but nevertheless detects BrdU. For this purpose, cells were pulsed for a short time by 5‐ethynyl‐2′‐deoxyuridine (EdU) which is incorporated into DNA. The nucleotide‐exposed ethynyl residue was then derivatized by a copper‐catalyzed cycloaddition reaction ("click chemistry" coupling) using a BrdU azide probe. The resulting DNA‐bound bromouracil moieties were then detected by commercial anti‐BrdU monoclonal antibodies without the need for a denaturation step. This method has been tested using several cell lines and is more sensitive than traditional BrdU and allows multicolor and multiplex analysis in flow cytometry (FCM) and image‐based cytometry. © 2015 by John Wiley & Sons, Inc.